High-Throughput Analytical Techniques for the Determination of the Residues of 653 Multiclass Pesticides and Chemical Pollutants in Tea, Part VII: A GC-MS, GC-MS/MS, and LC-MS/MS Study of the Degradation Profiles of Pesticide Residues in Green Tea. (27th November 2019) - Chang, Qiao-Ying; Pang, Guo-Fang; Fan, Chun-Lin; Chen, Hui; Yang, Fang; Li, Jie; Wen, Bi-Fang
Abstract: GC-MS, GC-tandem MS (MS/MS), and LC-MS/MS were used to mathematically define the degradation profiles of pesticide residues in two field trials. Nineteen pesticides were studied in the first field trial and 11 in the second. The results of the field trials demonstrated that the degradation profiles of pesticide residues in green tea can be described with power functions to successfully estimate the amount of time, following pesticide application, pesticide residues appearing in tea in concentrations at and/or above the maximum residue limit (MRL) decrease to concentrations below the MRL. Stability tests on green tea samples stored at room temperature were conducted to determine whether pesticide-incurred green tea samples prepared according to the method used in the field trials would be suitable for the preparation of reference standards for laboratory-proficiency testing trials. This paper reports the results of a GC-MS, GC-MS/MS, and LC-MS/MS study, as well as the suitability of the samples prepared under these conditions for use as pesticide reference standards in tea analysis.